2012
DOI: 10.1590/s0102-695x2012005000077
|View full text |Cite
|
Sign up to set email alerts
|

Bioprospecting for bioactives from seaweeds: potential, obstacles and alternatives

Abstract: Seaweeds are potential sources of high biotechnological interest due to production of a great diversity of compounds exhibiting a broad spectrum of biological activities. On the other hand, there is an urgent need for management options for a sustainable approach to the use of marine organisms as a source of bioactive compounds. This review discusses the bioprospection for bioactive seaweed compounds as pharmaceuticals and antifouling agents, encompassing their potential and possible obstacles and alternatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 122 publications
0
28
0
1
Order By: Relevance
“…This contrasted with a previous study by Quinderé et al (2013) who formerly reported the A. muscoides SPs physical and chemical characterization by agarose gel when Am-1 did not appear on gel and Am-3 had an intense metachromasia, as well as differing from other studied algae species SPs (Athukorala et al, 2006;Rodrigues et al, 2009;Rodrigues et al, 2011;Araújo et al, 2012).Thus, it was speculated that this algal species would perhaps biochemically change its Acta Scientiarum. Technology Maringá, v. 38, n. 3, p. 273-282, July-Sept., 2016 matrix polysaccharide composition according to the collection period (Zvyagintseva et al, 2003;Cardozo et al, 2007;Pereira & Costa-Lotufo, 2012). Regarding the PAGE procedure, there was no electrophoretic migration of the SPs fractions during the performance of three consecutive extractions, for any standard glycosaminoglycan observed, as a result of their high molecular masses (> 100 kDa) (Pomin, 2012;Fidelis et al, 2014;Mourão, 2015), except the 0.5 NaCl fraction (Am-1) that presented polydispersion as chondroitin-6-sulfate.…”
Section: Physical and Chemical Features Would Also Reflect The A Musmentioning
confidence: 99%
See 3 more Smart Citations
“…This contrasted with a previous study by Quinderé et al (2013) who formerly reported the A. muscoides SPs physical and chemical characterization by agarose gel when Am-1 did not appear on gel and Am-3 had an intense metachromasia, as well as differing from other studied algae species SPs (Athukorala et al, 2006;Rodrigues et al, 2009;Rodrigues et al, 2011;Araújo et al, 2012).Thus, it was speculated that this algal species would perhaps biochemically change its Acta Scientiarum. Technology Maringá, v. 38, n. 3, p. 273-282, July-Sept., 2016 matrix polysaccharide composition according to the collection period (Zvyagintseva et al, 2003;Cardozo et al, 2007;Pereira & Costa-Lotufo, 2012). Regarding the PAGE procedure, there was no electrophoretic migration of the SPs fractions during the performance of three consecutive extractions, for any standard glycosaminoglycan observed, as a result of their high molecular masses (> 100 kDa) (Pomin, 2012;Fidelis et al, 2014;Mourão, 2015), except the 0.5 NaCl fraction (Am-1) that presented polydispersion as chondroitin-6-sulfate.…”
Section: Physical and Chemical Features Would Also Reflect The A Musmentioning
confidence: 99%
“…Overall, our combined observations could reflect important biochemical aspects in the cell wall architecture polysaccharide composition of A. muscoides. However, further studies on the composition of these biomaterials in different periods of the year with possible impacts on their bioactivities should be conducted (Pereira & Costa-Lotufo, 2012).…”
Section: Sps From a Muscoides Discretely Delay The Apttmentioning
confidence: 99%
See 2 more Smart Citations
“…caulerpenin produced by green algae, lanosol, vidalol or elatol generated by red seaweeds, or dictyopterene C, pachydictyol A, fucodiphlorethol and epitaondiol produced by brown algae have attracted the attention of scientists for decades. [1] Except these, also the healthy lipids, i.e., mainly those containing the 'omega-3' long-chain polyunsaturated fatty acids, polar lipids as phospholipids/glycolipids with the positive health impact or healthy sterols can be very promising in terms of further use in food/feed industry. Recently, several papers focusing on the lipidomic characterization of marine resources have discussed this topic.…”
Section: Introductionmentioning
confidence: 99%